2018
DOI: 10.3389/fpls.2018.00895
|View full text |Cite
|
Sign up to set email alerts
|

Maize Combined Insect Resistance Genomic Regions and Their Co-localization With Cell Wall Constituents Revealed by Tissue-Specific QTL Meta-Analyses

Abstract: Combinatorial insect attacks on maize leaves, stems, and kernels cause significant yield losses and mycotoxin contaminations. Several small effect quantitative trait loci (QTL) control maize resistance to stem borers and storage pests and are correlated with secondary metabolites. However, efficient use of QTL in molecular breeding requires a synthesis of the available resistance information. In this study, separate meta-analyses of QTL of maize response to stem borers and storage pests feeding on leaves, stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 85 publications
3
29
0
Order By: Relevance
“…In the present study, LD declined rapidly below 0.2, reaching 0.1 at a distance of 26. 16 kb, suggesting there is potential for genome wide association studies and candidate gene selection [43]. A number of markers distributed on different chromosomes in the genome were in true LD and could serve the purpose.…”
Section: Patterns Of Linkage Disequilibriummentioning
confidence: 99%
“…In the present study, LD declined rapidly below 0.2, reaching 0.1 at a distance of 26. 16 kb, suggesting there is potential for genome wide association studies and candidate gene selection [43]. A number of markers distributed on different chromosomes in the genome were in true LD and could serve the purpose.…”
Section: Patterns Of Linkage Disequilibriummentioning
confidence: 99%
“…These are (i) MAS and MAB, (ii)Multiple resistance, (iii) Quantitative resistance (QR), (iv) Durable resistance, (v) Gene pyramiding and (vii) Gene stacking. MAS insects resistance in rice (Shabanimofred et al, 2015;Venkanna et al, 2018;Jaiswal et al, 2018) Striga resistance in sorghum (Yasir and Abdalla, 2013, Yohannes et al, 2015Ali et al, 2016), multiple insects resistance in maize (Badji et al, 2018) multiple resistances to herbicides (Gressel, 2000;Neve et al, 2009) Quantitative resistance (QR)…”
Section: Variants Of Plant Resistance To Pestsmentioning
confidence: 99%
“…Numerous studies have been conducted to map QTLs for resistance to European corn borer, Mediterranean corn borer, Asian corn borer, sugarcane borer, maize weevil, Southwestern corn borer, and fall army worm [34]. However, no information is available about the number, mode of action, and location of QTLs governing shoot fly resistance in maize.…”
Section: Plos Onementioning
confidence: 99%
“…The previous studies concluded that disease and insect resistance genes in maize appear in "clusters" [38]. The detected bins in the experiment (1.02-03, 1.09, 2.05, 6.00-6.01, 9.03 and 9.05-06) have been reported in different studies for insect resistance especially to European corn borer, fall army worm and maize weevil as presented in S1 Table. Based on meta QTL analysis, Badji et al [34] highlighted the presence of combined insect resistance genomic regions in maize and thus, could form the basis for multiple pest's resistance breeding. This…”
Section: Plos Onementioning
confidence: 99%